SPECIFIC FEATURES OF DEVELOPING DIGITAL ECONOMY IN THE NORTH-WEST FEDERAL DISTRICT: CHALLENGES AND PROSPECTS - Elena V. Erohina; Galina Yu. Gagarina (Вестник Российского экономического университета имени Г. В. Плеханова)
Digital economy provides great opportunities for the development of regional entities in all fields of activity. However, digitalization processes are connected with inevitable problems, uncertainty and risks. Digital economy can create new opportunities for citizens of the Russian Federation, such as getting state services, increasing the level of information openness and accessibility, cutting bureaucratic barriers. The article investigates the key lines in digitalization in the North-West Federal district. It was found out that in all 11 entities of the Federal district necessary legislative acts, strategies and other program documents for digital transformation are available. These documents are aimed at stimulating and developing digital technologies. Digital economy needs competent experts. Thus it is essential to create conditions for personnel training, education system and labour market upgrading. The impact of digital transformation on social and economic processes is obvious, however, a lot of its aspects are still poorly investigated. Academic research pays insufficient attention to digital change influence on innovation activity of regional entities, staff and information security. The article analyzes different criteria affecting the potential development of digital economy and social and economic development of the North-West Federal district. This analysis gave an opportunity to demonstrate prospects of the Federal district further development. The research findings can be used in the process of designing and amending regional strategic programs of developing digital society and as a material for further theoretical and practical research in the field of digital processes development in regional systems.